Sonic geographies: Themes, concepts, and deaf spots. Issue 7 (21st May 2018) - Paiva, Daniel
Abstract: This article poses a straightforward question: What has geography been listening to? Sonic geographies have been established as a relevant subfield in Human Geography in the last decades. During this period, a significant amount of work has been published, but there are still few reviews of these works, and most of them focus solely on Anglophone geography. In this article, I attempt to address this gap by providing an overview of the themes and concepts that have been studied within the emerging subfield of sonic geographies. My intention is to reunite a large range of works that are becoming increasingly scattered and specialized, in order to make sense of the subfield as a whole. With this in mind, I am particularly interested in identifying the "deaf spots" of the subfield, that is, the subjects, concepts, or fields that have not yet been explored thoroughly by sonic geographies.